Educational, developmental and psychological outcomes of resettled refugee children in Western Australia: A review of School of Special Educational Needs: Medical and Mental Health input. (27th June 2014) - Mace, Ariel Olivia; Mulheron, Shani; Jones, Caleb; Cherian, Sarah
<x xml:space="preserve">Abstract</x> Aim There are limited data regarding the educational backgrounds and associated psychological and developmental outcomes of refugee children resettling in Western Australia (WA). The WA paediatric Refugee Health Service (RHS) revised its first consult questionnaire (August 2011) to increase educational and psychosocial documentation, concurrent with engagement of a School of Special Educational Needs: Medical and Mental Health (SSEN: MMH) liaison teacher. This study aims to utilise these data to increase understanding of this cohort's educational, developmental and psychological needs and to describe SSEN: MMH's role within the RHS. Methods Retrospective audit and analyses were performed on all initial standardised questionnaires for school‐aged refugee children (4–18 years) and SSEN: MMH referrals between August 2011 and December 2012. Results Demographic data from 332 refugees are described (mean age 9.58 ± standard deviation 3.43 years). Detailed educational information was available for 205 children. Prior education was limited (median 2 years), 64.9% experienced likely schooling interruption and 55.8% received education in their primary language. Language development concerns were significantly associated with previous education in a second language (odds ratio (OR) 4.55, P < 0.05). Other severe developmental and schooling issues were uncommon at presentation, with few correlations to prior education. In contrast, several migration factors, including family separation and mandatory detention, were significantly associated with psychological comorbidities such as post‐traumatic stress disorder (OR 5.60, P < 0.001 and OR 14.57, P < 0.001, respectively). SSEN: MMH reviewed 59 complex cases. Referral was significantly associated with multiple educational, developmental and psychological concerns. Conclusions Refugee children have varied migration, trauma and educational backgrounds, impacting on health and psychological outcomes. In‐depth multidisciplinary history including prior education and psychosocial issues is recommended. Partnering with education services appears to play an effective, multifaceted role in aiding resettlement; however, longitudinal studies are required.